Analysis of QRIS Payment System Financial Literacy and Financial Management Performance on the Development of MSMEs - Hamdan, Hamdan; Adiyanto, Yoga; Sunaryo, Deni (Ilomata International Journal of Management, 2024)
Research purposes This is for analyze use system QRIS payments, literacy finance, performance management. Types of research This is descriptive quantitative, data collection using instrument study with those who have determined based on development theory between variable. Population in research This as many as 85 perpetrators businesses in the district Pandeglang and all over perpetrator as many as 85 business actors were created sample data observation. The data analysis method uses interpretation SPSS statistics 25. Research results show that QRIS, Literacy finance, Performance Management finance No influential or not impact to development MSME income in the sub-district Pandeglang. Recommendation for research Next, you can adding variables like variable satisfaction, attitude in use, motivation usage, and others so that expected results study the later can become donation thoughts and materials consideration so that you can increase use of QRIS. Implications Of these variables, financial literacy has the greatest influence on interest in using QRIS. Therefore, the government needs pay attention to and strengthen policies, especially in the field of financial literacy, as the main factor in increasing the interest of MSMEs and the public in using QRIS as a means of payment transactions.